Handbuch Hochschullehre Digital: Leitfaden für eine moderne und mediengerechte Lehre - Handke, Jürgen (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Digitisation of teaching has been an important topic at universities for years, but even after the Corona crisis, it has still not become widely accepted.With this revised guide, Prof. Dr. Jürgen Handke shows ways in which the entry into digitisation can succeed. Starting with problems of university teaching, he discusses the possibilities of media use and generation with the help of concrete examples, now also with the help of modern AI assistance systems. His proposals can overcome the problems of classical university teaching so that significant added value can be created in the interplay of proven analogue concepts and digital forms of mediation.Prof. Dr. Jürgen Handke operates the largest digital learning platform in his subject, linguistics, and is the producer of numerous teaching videos. Handke has received several awards for his inverted classroom models and his online teaching, including the Hessian Teaching Award, the Ars legendi Award for Digital Teaching and Learning and the OER Award. His projects H.E.A.R.T. and RoboPraX are milestones for the use of humanoid robots in teaching. Also published by the author: Humanoide Roboter. Showcase, Partner und Werkzeug (2020).